PENGARUH STRUKTUR MODAL DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN MANUFAKTUR TAHUN 2016-2018 - Ida Nurhayati; Andi Kartika; Intan Agustin (Dinamika Akuntansi Keuangan dan Perbankan, 2020)
The aim of this studies to know the influence of capital structure and profitability on company’s value with dividend policy as a moderation variable. The sampling method used purposive sampling with the observation period from 2016-2018. Data analysis was performed using multiple linear regression. This study resulted in the capital structure and dividend policy not having an effect on firm value. Profitability has an effect on firm value. Dividend policy is able to moderate the effect of capital structure on firm value. Dividend policy is unable to moderate the effect of profitability on firm value. Keywords: Company’s Value, Capital Structure, Profitability, and Dividend Policy